The Effect of Teachers' Training, Areas of Expertise, and Education Type on the Achievement of Multiple-choice HOTS Questions in Vocational High School - Sutrisno, Sutrisno (Fakultas Teknik Universitas Negeri Malang, 2021)
Abstract: This research aimed to find the impact of teachers' training, areas of expertise, and education type on the achievement of multiple-choice HOTS questions. The design of this research was experimental. The independent variable was training provision, the moderator variables were teachers' areas of expertise and education level, and the dependent variable was the achievement of multiple-choice HOTS questions. The subjects in this research were 28 teachers of SMKN 2 Turen, consisting of teachers in productive and non-productive areas of expertise. The data collection used documentation and assignments. The data analysis technique used descriptive statistics with a paired t-test and factorial f-test. The significance level in this research was p = 0.05. Results showed that (1) training provision significantly improved teacher's skill in making multiple-choice HOTS questions, (2) improvement tendency of productive teachers after training compared to non-productive teachers, albeit insignificant, and (3) improvement tendency shown by teachers from the non-teaching institutions after training compared to teachers from teaching institution, although also insignificant